Linguistic Compression in Saving Private Ryan Film in Indonesian Subtitle - Lilik Istiqomah; Yudi Hartanto; Tika Fatmalasari (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2020)
This research aims to analyze the linguistic compression in the film Saving Private Ryan in the Indonesian subtitle on the speech acts. This research uses descriptive qualitative method. The source of data is the conversation among characters in the film Saving Private Ryan. Meanwhile, data of this research are the utterances or sentences in the subtitle of the movie which involve two different languages; English (Source Language) and Indonesian (Target Language). The finding shows that there are 22 data of illocutionary speech acts which are translated by using linguistic compression technique and categorized into three types of illocutionary acts. The quality of the subtitles translated by that technique is very good because it translated accurately, the meaning or intention in words can be accurately delivered into the target language.